IPTEKS BANTUAN SOSIAL BERDASARKAN STANDAR AKUNTANSI PEMERINTAHAN DI KANTOR WILAYAH KEMENTERIAN AGAMA PROVINSI SULAWESI UTARA - Radjak, Yustanti A.; Kojo, Oliviana; Lacoro, Dian Ardhina; Morasa, Jenny (Universitas Sam Ratulangi, 2018)
Social assistance is the provision of assistance in the form of money or goods provided from the Central Government to the Regional Government or central institutions in the region. The expenditure / burden of social assistance in the Regional Office of the Ministry of Religion of North Sulawesi Province is in accordance with Government Accounting Standards (GAS). for procedures for social assistance that have been going well, can be seen from the procedures stipulated in the proposal until the disbursement of funds or goods. Presentation of financial statements using accrual methods makes it easier for the government to produce accurate government financial reports.Keywords: Government Accounting Standards, Social Assistance